The determinants of digital literacy among accounting students in a TVET Institution. - Salem, Natasha Afina; Asat, Siti Haliza; Ahmad, Nurul Fatihah (Jurnal Penyelidikan Sains Sosial, 2025)
Digital literacy is crucial in today’s world, influencing career opportunities, productivity, and education. As Malaysia moves towards a technology-driven economy, improving digital skills, especially among technical and vocational education (TVET) students, is essential. This study focuses on accounting students at Politeknik Mukah, Sarawak, to examine how attitude, social norms, and self-efficacy influence digital literacy. Mukah, a growing educational hub with institutions like Politeknik Mukah was chosen for this research. Using Social Cognitive Theory (SCT), the study surveyed 136 Diploma in Accountancy students through online surveys, distributed via Google Forms, email, and WhatsApp. The analysis shows that attitude and self-efficacy significantly boost digital literacy, while social norms have little impact. Hypothesis testing reveals a strong correlation between attitude and digital literacy, suggesting that a positive outlook enhances digital skills. Social norms, however, have minimal influence, indicating that societal expectations do not greatly shape students' digital capabilities. Self-efficacy stands out as the most influential factor, highlighting the importance of students' confidence in their abilities to improve digital literacy. This research expands on the application of Social Cognitive Theory in TVET education and provides valuable insights for educators and policymakers. It underscores the need for strategies that promote confidence and positive attitudes towards technology, ensuring a digitally skilled future workforce. Future studies could involve larger samples and longitudinal methods to track digital literacy development and uncover additional influencing factors across different educational contexts.